Development of a mathematical model of the diffusion and reaction of soot and Nox in a soot-coated catalyst particle - Diokno, Maria Rosa E.
A model of diffusion and reactions of oxygen and NOx ion a soot-coated copper modified ZSM-5 particle was developed. A single particle of Cu-ZSM-5 was preloaded with soot and exposed to different operating conditions. Runs were made using different NO and O2 concentrations, operating temperatures and capture rates. The individual reactions occurring in the soot layer and catalyst core were also monitored. In order to accomplish this a numerical scheme based on the method of lines technique and Chebyshev collocation and a differential algebraic equations solver to integrate in time was used. From the runs made, it was found that at particular operating conditions, there exists a range of reactant concentrations and that can used. It was also found that changes in temperature greatly affects the soot removal rate. The model's behavior closely resembles the results of the rotating fluidized bed experiments that inspired this study.